Polska opinia publiczna wobec działań PKW w Afganistanie i Iraku - Lorenc, Magdalena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The attitude of public opinion in Poland towards the activity of the Polish Military Contingent (PMC) in Afghanistan and Iraq was initially (in 2001-2002) quite enthusiastic. This was the consequence of solidarity with the United States after the terrorist attacks on the WTC and the Pentagon. However, even then the majority of respondents were skeptical about the Polish Army’s involvement in the ‘war on terror’. As time passed by a majority of Polish society no longer believed that Poland would obtain any political or financial benefits. The conviction that the losses had prevailed over the benefits emerged at the end of 2003 and it remained until the PMC deployment in Iraq ended. The benefits were only perceived in terms of the global image of Poland.